(untitled) (Nativa, 2024)
Oil activity in Ecuador is one of the main causes of soil contamination and represents a significant threat to the environment and human health. This study addresses the evaluation of the phytoextraction of heavy metals from the Amazonian Region in the province of Orellana in the Flor del Pantano Community with three grass species for tropical climates for three months: Guinea (Panicum maximum), Marandú (Brachiaria brizantha) and Mombaza (Panicum maximum), previously a soil analysis of cadmium, lead, cobalt, mercury and total chromium concentrations was performed, a one-way ANOVA experimental design was applied for the phytoextraction of heavy metals. In the result of the soil analysis of heavy metals, total chromium does not meet the permissible values of the Ministerial Agreement 097 anexo 2 book VI of Ecuador; the three species were evaluated against the control especially the concentrations of total chromium (Cr), where the extraction capacity in the different tests against the control showed the highest extractive capacity is Marandú, reaching an average of 12.65 mg kg-1 of Cr, almost twice as much as other species studied. This could be attributed to its adaptation to adverse conditions, such as acid soils with pH 5, Marandú’s physiological response, and its effectiveness in phytoextraction. Highlighting the importance of the use of grass species, it is essential to consider the specific characteristics of the species in future research, such as incorporating organic matter to promote microorganisms and improve the effectiveness of grasses. Keywords: phytoextraction, heavy metals, grasses, oil activity, plant biotechnology, sustainable environmental management. Fitoextracção de metais pesados em solos contaminados por actividades petrolíferas na Amazónia, Equador RESUMO: A atividade petrolífera no Equador é uma das principais causas de contaminação do solo e representa uma ameaça significativa ao meio ambiente e à saúde humana. Este estudo aborda a avaliação da fitoextracção de metais pesados da Região Amazónica na província de Orellana na Comunidade Flor del Pantano com três espécies de gramíneas para climas tropicais durante três meses: Guiné (Panicum maximun), Marandú (Brachiaria brizantha) e Mombaza (Panicum maximun), previamente foi realizada uma análise de solo das concentrações de cádmio, chumbo, cobalto, mercúrio e cromo total, foi aplicado o delineamento experimental ANOVA one-way para a fitoextração de metais pesados. No resultado da análise do solo de metais pesados, o crómio total não cumpre os valores admissíveis do Acordo Ministerial 097 anexos 2 livro VI do Equador, as três espécies foram avaliadas contra o controlo, especialmente as concentrações de crómio total (Cr), onde a capacidade de extração nos diferentes testes contra o controlo mostrou que a maior capacidade extractiva é Marandú, atingindo uma média de 12,65 mg/kg Cr, quase o dobro das outras espécies estudadas. Isso pode ser atribuído à sua adaptação a condições adversas, como solos ácidos com pH 5, à resposta fisiológica do Marandú e à sua eficiência na fitoextração, destacando a importância do uso de espécies de gramíneas, é essencial considerar as caraterísticas específicas a utilização de espécies de plantas em futuras investigações, tais como a incorporação de matéria orgânica para promover os microrganismos e melhorar a eficácia das gramíneas. Palavras chave: fitoextracção; metais pesados; gramíneas; atividade oleosa; biotecnologia vegetal; gestão ambiental sustentável.